The Environmental and Educational Topics in Agricultural TV Broadcasts - Šarkovic, Aleksandra; Matić, Jovanka; Bogdanov, Natalija (Eastern European Countryside, 2024)
The sustainable use and efficient management of natural resources are reflected in the introduction of modern production practices and agro-ecological measures. The new challenges facing farmers require new approaches to the transfer of agricultural knowledge, technologies and information. Television is an important medium for providing timely information and communication with farmers in developing countries, where other sources of information are less available. Therefore, television represents one of the most relevant sources of raising public awareness and concern for the environment. This paper seeks to investigate whether and to what extent specialised TV programmes for farmers of four national TV networks in Serbia cover topics related to the agro-environment. Content analysis was employed to determine the differences in the offer of environmental and educational contents of agricultural TV programmes broadcast by public and commercial television stations in Serbia. Research results reveal significant differences between public and commercial broadcasters in terms of the topics covered, which are especially evident with regard to environmentally and educationally related contents. As the educational value of the content is determined by the choice of subjects, a difference in the frequency with which certain groups of subjects are shown speaking in broadcasts is also noted.